2019
DOI: 10.1002/admi.201900752
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Recent Advances in 2D Stanene Nanosheets

Abstract: for example, incompatibility with the semiconductor industry, [13] toxicity, [14] and susceptibility to oxidative environments. [7] Accordingly, researchers are on the lookout for other existing or synthetic 2D analogues.There have been numerous reports describing a wide variety of layered ultrathin 2D nanomaterials beyond graphene, with fascinating and technologydriven properties. These single-layer atomic crystals are classified in terms of their constituent elemental bonding states and structures. Most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 235 publications
0
31
0
Order By: Relevance
“…Several TMDO heterostructure (HS) exhibit enhanced electrical and optical performances as compared to heterostructures consisting only of organic or inorganic materials . It is worth noting that by manipulating out‐of‐plane surface (i.e., replacing S atom by Se atom) in MoS 2 and other 2D material, such as stanene, can exhibit immense potential for future spintronic system . In addition, the key advantage of the HS lies in a complete freedom of material choice in the hetero‐stacks, due to the weak vdW interlayer interaction and each layer can be freestanding through “ideally” clean interface .…”
mentioning
confidence: 99%
“…Several TMDO heterostructure (HS) exhibit enhanced electrical and optical performances as compared to heterostructures consisting only of organic or inorganic materials . It is worth noting that by manipulating out‐of‐plane surface (i.e., replacing S atom by Se atom) in MoS 2 and other 2D material, such as stanene, can exhibit immense potential for future spintronic system . In addition, the key advantage of the HS lies in a complete freedom of material choice in the hetero‐stacks, due to the weak vdW interlayer interaction and each layer can be freestanding through “ideally” clean interface .…”
mentioning
confidence: 99%
“…As a typical topological 2D material, 2D Sn significantly differs from stannum-based materials such as stannum protoxide and stannum oxide, characterizing particular physicochemical properties such as tunable bandgaps, chiral phases, strong spin–orbit coupling, and quantum spin Hall effect via its stable buckled structures [ 22 ]. Until now, the main synthesis method of Sn material is to deposit Sn onto various substrates through physical vapor deposition (PVD) [ 22 ]. Zhu et al [ 23 ] reported the first successful preparation of 2D SnNSs on the surface of Bi 2 Te 3 (111) substrate via molecular beam epitaxy (MBE), paving the avenue for further experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [ 23 ] reported the first successful preparation of 2D SnNSs on the surface of Bi 2 Te 3 (111) substrate via molecular beam epitaxy (MBE), paving the avenue for further experimental studies. Moreover, some other researches also have achieved Sn growth on semiconductor Si(111) and InSb(111) substrate [ 24 , 25 ], metal substrates (e.g., Pt, Au, Ag, Cu, Al, Ni, Pd, Ir) [ 22 ], and semimetallic Sb(111) substrate [ 26 ] under ultrahigh vacuum (UHV) ambiance. Nevertheless, these prepared 2D Sn materials through epitaxial growth approaches suffer from some drawbacks, such as vertical scale inhomogeneity and scalable synthesis limitation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the discovery of graphene and other two-dimensional atomic crystals, the search for new 2D nanomaterials with unusual electrophysical properties began, as well as the development of various electronic devices based on it [13]- [15]. Various technological methods for synthesizing two-dimensional monoatomic crystals based on elements of the fourth group of the periodic table are already known: germanene [16], silicene [17], borophene [18], stanene [19], phosphorene [20], etc., as well as 2D crystals based on carbides, oxides, chlorides, nitrides, transition metal dichalcogenides, etc. [21].…”
Section: Introductionmentioning
confidence: 99%